Association of tumors having Epstein–Barr virus in surrounding lymphocytes with poor prognosis. (21st June 2022) - Yogi, Norikazu; Usui, Genki; Matsusaka, Keisuke; Fukuyo, Masaki; Fujiki, Ryoji; Seki, Motoaki; Takano, Shigetsugu; Abe, Hiroyuki; Morikawa, Teppei; Ushiku, Tetsuo; Ohtsuka, Masayuki; Kaneda, Atsushi
Abstract: Infection with certain viruses is an important cause of cancer. The Pan‐Cancer Analysis of Whole Genomes (PCAWG) Consortium recently analyzed the whole‐genome sequencing (WGS) data from 2656 cases across 21 cancer types, and indicated that Epstein–Barr virus (EBV) is detected in many different cancer cases at a higher frequency than previously reported. However, whether EBV‐positive cancer cases detected by WGS‐based screening correspond to those detected by conventional histopathological techniques is still unclear. In this study, to elucidate the involvement of EBV in various cancers, we reanalyzed the WGS data of the PCAWG cohort combined with the analysis of clinical samples of gastric and pancreatic cancer in our cohort. Based on EBV copy number in each case, we classified tumors into three subgroups: EBV‐High, EBV‐Low, and EBV‐Negative. The EBV‐High subgroup was found to be EBV‐positive in the cancer cells themselves, whereas the EBV‐Low subgroup was EBV‐positive in the surrounding lymphocytes. Further, the EBV‐Low subgroup showed a significantly worse prognosis for both gastric cancer and across cancer types. In summary, we classified tumors based on EBV copy number and found a unique cancer subgroup, EBV‐positive in the surrounding lymphocytes, which was associated with a poor prognosis. Abstract : Considering the strong relationship between viruses and cancer, and the potential role of Epstein‐Barr virus (EBV) in different cancers, this study examined the involvement of EBV in various cancers based on the reanalysis whole‐genome sequencing data from the PCAWG cohort combined with the analysis of clinical samples of gastric and pancreatic cancer in our cohort. Based on EBV copy numbers in each case, we identified three subgroups of cancer: EBV‐High with EBV in the cancer cells, EBV‐Low with EBV in the surrounding lymphocytes, and EBV‐Negative subgroups. The EBV‐Low is a unique cancer subgroup showing a significantly worse prognosis in gastric cancer and across cancer types.